Problematika Pemanfaatan Media Pembelajaran Berbasis TIK di Madrasah Ibtidaiyah - Nila Nimatul Lailiyah; Shibi Zuharoul Mardliyah (Bidayatuna, 2021)
Islamic Education (PAI) was one of the method to give the Islamic values toward students. It was very important to be taught among the students that without any compulsions and who had high interest. The usage of learning medium was one of the effort in stimulating the students' interest. But, from this aim, there were some obstacles among the teachers in implementation, particularly the ICT based, moreover in the pandemic Covid-19 that force the students to learn "at home". This research was to know the issues about the usage of medium learning that ICT based on the PAI Lessons. The research was descriptive analysis through interview, observation and documentation, which described the field condition about the usage issues of learning medium PAI ICT based. The research result showed that the school facilities were needed to be develop for the sake of achieving to optamize the teachers' skill on the usage of learning medium ICT based. This was very important to be developed as the subject for developing a certain theory as one of factor was unlinier educational background and the paradigm that PAI learning would be effective through the conventional method.